Is HNF4A gene, a risk factor or protection against coronary artery disease?. (14th October 2021) - Temtem, M; Serrao, M; Mendonca, M I; Santos, M; Sousa, A; Mendonca, F; Sousa, A C; Henriques, E; Freitas, S; Rodrigues, M; Borges, S; Guerra, G; et al.
Abstract: Background: Hepatocyte nuclear factor4 A (HNF4A) gene was considered by GWAS associated with atherosclerosis and CAD susceptibility. Loss-of-function mutations in human hepatocyte nuclear factor 4α (HNF4α), a transcriptor factor encoded by the HNF4A gene, are associated with maturity-onset diabetes of the young and lipid disorders. However, the mechanisms underlying the lipid disorders are poorly understood. Aim: We propose identifying the genetic predisposition to atherosclerosis progression and events occurrence or regression and better prognosis, through a cohort study from GENEMACOR population. Methods: We investigated a cohort of 1, 712 patients who underwent coronary angiography with more than 70% stenosis of at least one main coronary vessel. 33 SNPs associated with the risk of CAD in previous GWAS were genotyped by TaqMan assays methodology. We evaluated the best genetic model associated with CAD prognosis (events) with a 95% CI in bivariate analysis. The hazard function was performed by a Cox survival regression model adjusted for age, sex, type 2 diabetes, hypertension, and hypercholesterolemia, to evaluate their relationship with the event's incidence. Finally, we constructed Kaplan–Meier cumulative-event curves for the significant genetic variants. Results: Our evaluation revealed a SNP paradoxically associated with protection from atherosclerosis progression and events occurrence: rs1884613 C>G in the HNF4A gene on chromosome 20 dominant model [OR=0.653; 95% CI (0.522–0.817); p=0.0002]. Cox survival regression model showed a CAD protective effect of HNF4A with a Hazard ratio (HR) of 0.771; p=0.007. The Kaplan-Meier cumulative event analysis disclosed that the CG+GG vs CC genotype of rs1884613 HNF4α was associated with a better prognosis (Breslow test, p=0.004) at the end of the follow-up. Conclusion: We identified, in this study, one SNPs paradoxically associated with a better CAD prognosis rs1884613 in HNF4A. The HNF4A gene variants could induce loss of HNF4α function, modifying and modulating hepatic lipase and lipid metabolism conferring a beneficial effect on atherosclerosis progression and events occurrence. Funding Acknowledgement: Type of funding sources: None.